Drug Utilization Study of Lopinavir And Ritonavir In Covid-19 Patients - Aryani, Toetik; D. Puspitasari, Arina; Nafikhah, Wardah Zuhan; Rosyid, Alfian Nur; Astanti, Erika (Syntax Corporation, 2022)
The world pandemic of COVID-19 which caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a very infectious and contagious. Lopinavir and ritonavir is recommended based on guidelines from National Health Commission of China as an antiviral therapy for COVID-19. Both lopinavir and ritonavir inhibit the 3CLpro enzyme’s action, which its role in replication also release of viruses. As protease inhibitor in Human Immunodeficiency Virus (HIV), both lopinavir and ritonavir’s target is a symmetrical bag of C2 where does not exist in 3CLpro enzyme of corona virus. This literature review is needed to determine the outcome of using lopinavir and ritonavir in order to find a conclusion that can be used as a basis for intervening drug administration in patients of COVID-19. A method of narrative review was used in this study which was carried out by searching on Pubmed and Science direct. After doing abstract screening and title based on the inclusion criteria, 13 articles were left to be analyzed. These articles were analyzed using predetermined clinical outcome parameters, namely duration of hospital stay, composite event, clinical symptom score, time to achieve negative RT-PCR, duration of mechanical ventilation, and all-cause mortality. Based on all reviewed articles, the majority of clinical outcome parameters showed that the outcome was no better than standard care or other drugs. From this review, it can be concluded that lopinavir along with ritonavir provide no better clinical outcomes than standard therapy or other drugs in COVID-19’s patients.